Five minds for the future. - Gardner, Howard, 1943- (Boston : Harvard Business Press, 2008)
We live in a time of vast changes. And those changes call for entirely new ways of learning and thinking. In "Five Minds for the Future," Howard Gardner defines the cognitive abilities that will command a premium in the years ahead: the Disciplinary mind--mastery of major schools of thought (including science, mathematics, and history) and of at least one professional craft; the Synthesizing mind--ability to integrate ideas from different disciplines or spheres into a coherent whole and to communicate that integration to others; the Creating mind--capacity to uncover and clarify new problems, questions, and phenomena; the Respectful mind--awareness of and appreciation for differences among human beings and human groups; and the Ethical mind--fulfillment of one's responsibilities as a worker and citizen. World-renowned for his theory of multiple intelligences, Gardner takes that thinking to the next level in this book, drawing from a wealth of diverse examples to illuminate his ideas. Concise and engaging, "Five Minds for the Future" will inspire lifelong learning in any reader and provide valuable insights for those charged with training and developing organizational leaders--both today and tomorrow.
Inhoudsopgave : 1. Minds viewed globally 2. The disciplined mind 3. The synthesizing mind 4. The creating mind 5. The respectful mind 6. The ethical mind 7. Conclusion
Keywords: Denken; Intelligentie